PROSES PENYELESAIAN PERKARA HARTA BERSAMA DI PENGADILAN AGAMA - Mahardhita, Gempur (An Nawawi, 2021)
When a marriage is terminated, a new legal effect arises. One of the legal impacts that arise is that the distribution of joint assets is required. Joint assets in marriage are property acquired during the marriage, this is as regulated in Article 35 paragraph (1) of Law Number 1 of 1974 concerning Marriage which reads "property acquired during marriage becomes joint property". The distribution of joint assets for Indonesian citizens who are Muslim is carried out in the Religious Courts. This is as regulated in articles 49 and 50 paragraph (2) of Law Number 3 of 2006 concerning Amendments to Law Number 7 of 1989 concerning Religious Courts. The article essentially states that when there is a dispute over property rights between people who are Muslim related to marriage, endowments, zakat, inheritance, wills, infaq, sharia economics and shadaqah, the dispute is decided by the religious court. In its implementation, the settlement of the distribution of joint assets will go through the stages regulated by the Civil Procedure Code. This stage will be the basis for the panel of judges to give a decision related to the case being examined.